Assessing the thermal stability of toolmarks casting materials through optical comparison microscopy, virtual comparison microscopy and quantitative similarity scores - Alaric C. W. Koh; Kai Yuan Yeoh (Oxford University Press, 2022)
Toolmarks, particularly those found on bulky, inaccessible or immovable items, can be recovered by casting. To allow for subsequent comparative examinations, the casting material, typically polysiloxanes or silicones, must be able to capture and preserve fine details within a toolmark accurately. To study the stability of such details after exposure to heat, toolmark casts were heated at either 60 °C for 2 h, or 90 °C for 1 h. These casts were subsequently compared to casts that had not been exposed to heat, using traditional optical comparison microscopy, as well as virtual comparison microscopy. Digitised toolmark signatures were also extracted from the casts and compared pairwise to obtain quantitative similarity scores based on cross-correlation, consecutive matching striae and Mann-Whitney U-statistic. Our results show that the fine surface details captured on all four commercial toolmark casting materials tested herein remained stable after exposure to heat. This study shows that the above heating protocols are viable viral inactivation methods for toolmark casts that are potentially contaminated with human coronaviruses, such as SARS-CoV-2. Our findings also apply to other scenarios, such as for casts that were left in a vehicle parked under the sun.